Prognostic significance of the pretreatment pan-immune-inflammation value in colorectal cancer patients: an updated meta-analysis - Jing Li; Huayang Pang; Hao Sun; Xiaoyu Liu (Frontiers in Oncology, 2025)
BackgroundThe prognostic importance of the pretreatment pan-immune-inflammation value (PIV) in colorectal cancer has been extensively documented, yet its role remains unclear. This study aims to conduct an updated meta-analysis to elucidate the relationship between the pretreatment PIV and long-term survival outcomes among patients diagnosed with colorectal cancer.MethodsA systematic literature review was performed in PubMed, Embase, Web of Science and CNKI to identify eligible studies from inception to January 18, 2025. The primary endpoints evaluated were survival outcomes. Hazard ratios (HRs) along with their corresponding 95% confidence intervals (CIs) for survival outcomes were extracted. A random-effects model was utilized to synthesize the findings. All statistical analyses were conducted using R software, version 4.2.1.ResultsOut of 81 identified studies, a total of 14 retrospective studies including 6,192 colorectal cancer patients were ultimately included. In this meta-analysis, the pooled results demonstrated that patients with higher PIV exhibited significantly poorer overall survival (11 studies, HR=1.95; 95%CI:1.64-2.31; P<0.01; I2 = 34%) and disease-free survival (10 studies, HR= 1.89; 95% CI: 1.48-2.41; P < 0.01; I2 = 66%). Furthermore, evidence pooled from two studies demonstrated that PIV may be an independent prognostic factor for cancer-specific survival (HR= 2.61; 95% CI: 1.56-4.38; P < 0.01; I2 = 0%).ConclusionOur study reveals that the pretreatment PIV can serve as a valuable biomarker for predicting long-term survival outcomes in patients with colorectal cancer, which may have important clinical implications for personalized treatment strategies.